Tingkat Kepuasan Pasien Terhadap Pelayanan Obat di Instalasi Farmasi Puskesmas Bergas - Hubertus Silvia Anggrio Bili; Inge Mustika Aisah; Inanda Sofia Putri; Abdul Roni (Lembaga Pengembangan Kinerja Dosen, 2026)
Patient satisfaction is a key indicator for assessing the quality of pharmaceutical services in primary healthcare facilities. High-quality pharmacy services can improve patient trust, medication adherence, and therapeutic outcomes. This study aimed to evaluate patient satisfaction with pharmaceutical services at the Pharmacy Installation of Bergas Public Health Center, Semarang Regency. A descriptive quantitative study with a prospective approach was conducted involving 93 outpatients selected through accidental sampling. Data were collected using a questionnaire based on the five SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Responses were analyzed descriptively using a Likert scale. The findings showed that the overall patient satisfaction level reached 78.76%, indicating that patients were generally satisfied with the services provided. The highest scores were obtained in the empathy (81.81%) and reliability (81.70%) dimensions. Meanwhile, tangibles (78.18%), assurance (77.06%), and responsiveness (75.09%) were categorized as satisfactory. These results suggest that pharmaceutical services at Bergas Public Health Center have largely met patient expectations, particularly regarding staff competence, communication, and attention to patient needs. However, improvements in responsiveness and supporting facilities are still necessary to further enhance service quality and patient satisfaction.